Differences between murine arylamine N-acetyltransferase type 1 and human arylamine N-acetyltransferase type 2 defined by substrate specificity and inhibitor binding - Laurieri, N; Kawamura, A; Westwood, I; Varney, A; Morris, E; Russell, A; Stanley, L; Sim, E (BioMed Central, 2014)
Background: The mouse has three arylamine N-acetyltransferase genes, (MOUSE)Nat1, (MOUSE)Nat2 and (MOUSE)Nat3. These are believed to correspond to (HUMAN)NAT1, (HUMAN)NAT2 and NATP in humans. (MOUSE)Nat3 encodes an enzyme with poor activity and human NATP is a pseudogene. (MOUSE)Nat2 is orthologous to (HUMAN)NAT1 and their corresponding proteins are functionally similar, but the relationship between (MOUSE)Nat1 and (HUMAN)NAT2 is less clear-cut. Methods: To determine whether the (MOUSE)NAT1 and (HUMAN)NAT2 enzymes are functionally equivalent, we expressed and purified (MOUSE)NAT1*1 and analysed its substrate specificity using a panel of arylamines and hydrazines. To understand how specific residues contribute to substrate selectivity, three site-directed mutants of (MOUSE)NAT2*1 were prepared: these were (MOUSE)NAT2_F125S, (MOUSE)NAT2_R127G and (MOUSE)NAT2_R127L. All three exhibited diminished activity towards “(MOUSE)NAT2-specific” arylamines but were more active against hydrazines than (MOUSE)NAT1*1. The inhibitory and colorimetric properties of a selective naphthoquinone inhibitor of (HUMAN)NAT1 and (MOUSE)NAT2 were investigated. Results: Comparing (MOUSE)NAT1*1 with other mammalian NAT enzymes demonstrated that the substrate profiles of (MOUSE)NAT1 and (HUMAN)NAT2 are less similar than previously believed. Three key residues (F125, R127 and Y129) in (HUMAN)NAT1*4 and (MOUSE)NAT2*1 were required for enzyme inhibition and the associated colour change on naphthoquinone binding. In silico modelling of selective ligands into the appropriate NAT active sites further implicated these residues in substrate and inhibitor specificity in mouse and human NAT isoenzymes. Conclusions: Three non-catalytic residues within (HUMAN)NAT1*4 (F125, R127 and Y129) contribute both to substrate recognition and inhibitor binding by participating in distinctive intermolecular interactions and maintaining the steric conformation of the catalytic pocket. These active site residues contribute to the definition of substrate and inhibitor selectivity, an understanding of which is essential for facilitating the design of second generation (HUMAN)NAT1-selective inhibitors for diagnostic, prognostic and therapeutic purposes. In particular, since the expression of (HUMAN)NAT1 is related to the development and progression of oestrogen-receptor-positive breast cancer, these structure-based tools will facilitate the ongoing design of candidate compounds for use in (HUMAN)NAT1-positive breast tumours.